Theoretical and experimental investigations: Synergetic effect of Yb–Cu substitution on different properties of hexagonal ferrites. (November 2022) - Idrees, Mishal; Abbas, Faisal; Sadiq, Imran; Khan, Hasan M.; Sadiq, Farhan; Nadeem, Muhammad; Hussain, Sajjad; Riaz, Saira; Naseem, Shahzad
Abstract: This research project was designed to understand the synergetic effect of trivalent ion Yb 3+ and divalent ion Cu 2+ co-substitution on different properties of X-type hexagonal nano ferrites. For this purpose, a series of Sr2-x Ni2 YbX Fe28-Y CuY O46 X-type hexagonal nano ferrites with concentration (x = 0, 0.02, 0.06, 0.1 & y = 0, 0.1, 0.2, 0.3) was synthesized by adopting the sol gel method. The XRD (X-ray diffraction) results of synthesized samples reveal the formation of single phase for all samples with space group P63/mmc. All the XRD peaks coincided with the reference card (ICDD # 01-073-2034). The theoretical fitting was performed by implementing the Rietveld refinement method to further check the single phase of the samples. The crystallite size and unit cell volume decrease with increasing Yb 3+ and Cu 2+ contents. The VSM results indicated the hard magnetic nature of all the synthesized materials and theoretically calculated particle size was varied in the range between 9.2 and 11.5 nm. The saturation (Ms) and remanence magnetization (Mr) decreased with the increase in Yb–Cu contents. The value of coercivity (Hc ) was first increased and then decreased with the substitutions. Furthermore, the Law of approach to saturation (LAS) was employed to theoretically fit the hysteresis loops. The mixture of spherical and rod shape grains was observed in the SEM micrographs. By adopting the line intercept method, the calculated grain size was varied in the range from 0.691 to 1.33 μm. FTIR spectrum exhibits no extra absorption band due to residual material which also confirms the formation of single hexagonal phase structure. The Thermogravimetric (TGA) analysis divulged the weight losses due to removal of nitrate, vaporization of water molecules and removal of organic compounds at different temperatures. The reflection loss (RL) values have been enhanced with the substitution of Yb–Cu contents. Highlights: The Sol-Gel method was used to synthesize X-hexaferrites. The XRD analysis confirmed the single phase for all samples. The W–H technique was employed to calculate the microstrain. FTIR spectra also confirmed the single phase for all samples. The magnetization has been decreased with Yb–Cu substitution.